2010
DOI: 10.1111/j.1460-2695.2010.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thick DLC coating on fatigue behaviour of magnesium alloy in laboratory air and demineralised water

Abstract: A B S T R A C T Rotating bending fatigue tests have been performed using Diamond-like carbon (DLC) coated specimens of a wrought magnesium alloy, AZ80A, in laboratory air and demineralised water and the effect of DLC coating on fatigue and corrosion fatigue behaviour was studied. Three film thicknesses of 3.5 μm, 13 μm, and 25 μm (two-layer film) were evaluated and particular attention was paid to the role of thick DLC coating. In laboratory air, the fatigue strengths of the DLC-coated specimens were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In this case, however, the tendency of S-N diagram was irrelevant to the stress amplitude calculation methods. In addition, it is known that AZ80 has age hardenability, but it was confirmed that the effect of the thermal history during the DLC deposition on fatigue strength can be neglected [3]. Figures 6 (a) and (b) are SEM micrographs showing fracture surfaces near the crack initiation sites in the substrate and D15, respectively.…”
Section: Fatigue Strengthmentioning
confidence: 94%
See 2 more Smart Citations
“…In this case, however, the tendency of S-N diagram was irrelevant to the stress amplitude calculation methods. In addition, it is known that AZ80 has age hardenability, but it was confirmed that the effect of the thermal history during the DLC deposition on fatigue strength can be neglected [3]. Figures 6 (a) and (b) are SEM micrographs showing fracture surfaces near the crack initiation sites in the substrate and D15, respectively.…”
Section: Fatigue Strengthmentioning
confidence: 94%
“…As shown in Fig.6(b), a film defect exists at the crack initiation site of D15. The crack is believed to be generated in the substrate underneath the bottom of the film defects due to their stress concentration [3]. The DLC film around the crack initiation site does not peel off the substrate, indicating very good adhesion of the film.…”
Section: Fatigue Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…3(b). It has been reported that corrosion fatigue strengths largely decreased due to the penetration of corrosive environment through this kind of pin-hole defects of DLC film (Uematsu et al, 2010). Figure 4 shows the surface morphology of Ni-plating single-layered specimen, which macroscopically has smooth surface (Fig.…”
Section: Coating Appearancesmentioning
confidence: 99%
“…However, it should be noted that hybridcoating is not effective if the Ni-plating layer has large cracking in itself. The fractographic analyses of DLC singlelayered sample could be found elsewhere (Uematsu et al, 2010, Uematsu et al, 2015. …”
Section: Fractographic Analysesmentioning
confidence: 99%